Tuhan Dalam Lintasan Sejarah Filsafat Barat - Saidul Amin; Ayu Rustriana Rusli (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2021)
The purpose of writing this article is to discuss the nature of God, or demiurge – creator and designer of the cosmos, whom a venerable subject in philosophy and natural theology. This paper aims  to explore  the concept of God in the thought of Western Philosophy. The understanding of God in the East is different from the West. East is rich with mystical life, revealing the divine realm through inner experience. While in the West, reason has always been a command and a tool to meet the "ultimate truth". This study aims to explore the concept of God in Western philosophical thought. This study uses a style of literature through a qualitative approach based on the phenomena obtained in existing manuscripts. It was found by descriptive analysis that both early philosophers and modern philosophers in the West, when talking about God, always used an intellectual approach, namely using what is called a philosophical approach. Here there is an attempt by them to find God in absolute or absolute terms, by considering the possibilities for humans to arrive at the truth about God.